A nonstop mutation in the factor (F)X gene of a severely haemorrhagic patient with complete absence of coagulation FX - Ameri, Afshin; Machiah, Deepa K.; Tran, Thuy T.; Channell, Cynthia; Crenshaw, Valerie; Fernstrom, Karl; Khachidze, Manana; Duncan, Alexander; Fuchs, Sebastien; Howard, Tom E. (Thrombosis and Haemostasis, 2007)
We identified a previously unknown mutation by sequencing the factor (F)X gene in a severely haemorrhagic 14-year-old maleAfrican-American individual with undetectable plasma FX-activity and -antigen levels. This mutation, called F10-Augusta, was homozygote and is a combination of an 8bp insertion in flanking 3’-genomic-DNA and a 5bp terminal exon-8 deletion involving codons 437 and 438. Sequencing of RT-PCR and 3’-RACE products showed that the F10-Augusta transcript is normally processed but lacks an in-frame stop codon. An allele specific 3’-RACE-based RFLP assay demonstrated that the steady-state concentration of the mutant transcript was markedly lower than that of the wild-type message in total-RNA samples from the patient’s unaffected heterozygous parents. The recently discovered nonstop decay mechanism, a component pathway of the mRNA surveillance system, is a possible explanation for the reduced concentration of the mutant FX transcript. This is the first report implying such a mechanism in the pathogenesis of inherited bleeding disorders.
Keywords: Autosomal recessive; congenital bleeding disorder; mRNA surveillance; F10-Augusta